Умови конкурентоспроможності машинобудівного підприємства та роль ціни в їхньому забезпечені - Тимошик Н. С. (Видавництво Національного університету "Львівська політехніка", 2007)
Розглядаються чинники впливу на конкурентоспроможність підприємств. Ми проаналізували особливості їхнього формування в машинобудуванні. Обґрунтовано ступінь залежності ціни продажу від техніко-економічних параметрів продукції, співвідношення попиту і пропозиції на ринку, становище підприємства. Наведено особливості формування конкурентних переваг залежно від характеру коливань кон’юнктури ринку. The factors of influence on the enterprises’ competitive ability are observed. We have also analyzed the peculiarities of their formation in machinery manufacturing. Thereby, the level of dependence of the sale price from technical and economical parameters of the products and correlation of demand, proposition at the market and enterprise position are grounded. The peculiarities of formation of competitive advantages in accordance with the character of the changes of the market environment are presented.